Un frammento duecentesco della «Chirurgia» di Rolando da Parma volgarizzata (Carte Romanze, 2021)
A fragment of a Florentine translation of Rolando da Parma’s Chirurgia has recently been identified in the Archive of Bologna. In this paper the fragment will be described and information will be provided from a philological, linguistic and historical-cultural point of view in order to introduce the edition of the short extract.